The progress of peptide vaccine clinical trials in gynecologic oncology - Mi Tang; Jiang-Hui Cai; Hao-Yang Diao; Wen-Mei Guo; Xiao Yang; ShaSha Xing (Taylor & Francis Group, 2022)
Peptide vaccine are a type of immunotherapy that are synthesized according to the amino acid sequence of known or predicted tumor antigen epitopes. They are safe and well tolerated and have shown exciting results in gynecologic oncology. However, no peptide vaccine has yet been licensed in this field. This review examines peptide vaccine clinical trials in gynecology registered on ClinicalTrials.gov through January 1, 2022, analyzes the global progress and current achievements of peptide vaccines in gynecology, and explores the efforts focused on devising new methods to boost immunotherapeutic outcomes, including the use of adjuvants, multi-epitope vaccines, combinations of helper T cell epitopes, personalized peptide vaccines, synthetic long peptides, new peptide delivery, and combination therapy.